The Weight Gain and Growth of Crossbred Bulls Fed Locally Inspired Supplements Compared with Current Feeding Systems in Village Smallholdings in Malang, East Java. Issue 1 (April 2020) - Setiadi, D; Kusmartono,; Kasmiyati,; Mashudi,; Zakariya, A Z; Harper, K J; Poppi, D P
Abstract: Growth rates of cattle in village smallholder farms are often low (0, 2-0, 5 kg/d) due to the ration formulation not meeting the nutrient requirements for cattle to achieve their potential live weight gain. This experiment aims to determine the growth of crossbred bulls fed a range of supplemented diets using local products comparing them to current traditional feeding system. This village was conducted in Kucur village, Dau sub-district, Malang. Fifyt cross bred aged between 1.5-2 years were allocated into five treatments; cassava-based diet by recent ACIAR-UB experiment (T1), commercial concentrate (T2), YaYa diet (T3), Santos diet (T4) and current feeding system (CFS) by smallholder farmers (T0) as the control. Cassava-based diet (T1) consisted of 50% cassava, 25% copra meal (CM) and 25% palm kernel cake (PKC). Local concentrate (T2) was bought from local cooperative in Malang. Yaya diet (T2) consisted of 30% cassava, 20% corn cob, 20% copra meal, 20% palm kernel cake and 10% rice bran. Santos diet (T4) consisted of 40 % corn cob, 20% palm kernel cake 20% rice bran, and 20% wheat pollard. Control treatment (T0) was 1 kg wheat pollard a day which was the general current feeding system by local smallholders. The experiment found that cassava-based diet (T1) supplementation showed the highest body growth compared to the other diets.